AMERICAN CONSERVATIVE MOVEMENT OF THE TEA PARTY IN 2009: A CONCEPT OF FOUNDING - Didik Murwantono (Humaniora, 2013)
The awakening of American conservative movement like The Tea Party in the beginning of 2009 was a phenomenon as a reaction against Obama‘s Democratic presidency. American conservative movements have never been the same but they maintain a strong tradition. Historically, they have emerged and then died out. This research offers a concept of ‘founding’ for dealing with social changes and the political transformation of The Tea Party phenomenon. It adopts descriptive qualitative methods and applies Event Structure Analysis supported by Founding and Social Change theories. In general, American conservative movements have never been successful; however they have affected policy changes within the government and the political parties in the United States. They are known to be inconsistent, yet it seems likely that they will continue to evolve.